A longitudinal perspective on financial risk tolerance: rank-order and mean level stability. (27th July 2009) - Roszkowski, Michael J.; Cordell, David M.
We examined the temporal stability of financial risk tolerance in a sample of 36 students enrolled in an undergraduate financial planning program who had taken the test on the same day but took the retest anywhere from 269 days to 814 days later. Relative stability was around .56 after a period averaging about a year and .65 after a period averaging close to a year and a half. The test-retest correlation was .61 for the 26 cases where the test and retest occurred within a narrow range of 269 days to 288 days. In terms of absolute stability, there was an increase of about four points within the shorter time span and eight points under the longer duration. The reason for the increase is not clear. The relative stability of financial risk tolerance is comparable to other traits, suggesting that it is not as transitory as some have thought it to be.